In the moral eye of the beholder: the interactive effects of leader and follower moral identity on perceptions of ethical leadership and LMX quality - Giessner, Steffen R.; Van Quaquebeke, Niels; van Gils, Suzanne; van Knippenberg, Daan; Kollée, Janine A. J. M. (Frontiers in Psychology, 2015)
Previous research indicated that leader moral identity (i.e., leaders’ self-definition in terms of moral attributes) predicts to what extent followers perceive their leader as ethical (i.e., demonstrating and promoting ethical conduct in the organization). Leadership, however, is a relational process that involves leaders and followers. Building on this understanding, we hypothesized that follower and leader moral identity (a) interact in predicting whether followers will perceive their leaders as ethical and, as a result, (b) influence followers’ perceptions of leader–follower relationship quality. A dyadic field study (N = 101) shows that leader moral identity is a stronger predictor of followers’ perceptions of ethical leadership for followers who are high (vs. low) in moral identity. Perceptions of ethical leadership in turn predict how the quality of the relationship will be perceived. Hence, whether leader moral identity translates to perceptions of ethical leadership and of better relationship quality depends on the moral identity of followers.